O gerenciamento de resíduos sólidos hospitalares: - Oliveira, Ivaneide de Sousa (Universidade Federal do Tocantins, 2023)
The proper disposal of solid waste , a theme that stands out today , mainly by consumption and accumulation of waste , causing environmental impacts . However , science seeks to propose solutions that reduce environmental impacts and / or aware involved the need for management of solid waste , in the case of RSS management is very important , because the risks are even greater , whether chemical, physical or biological thus there is a need to plan systematically and managed way the flow of handling RSS .